1859 Terr. of N.M. Laws 94-96, § 3 - (:unkn) unknown (My University, 1859)
An Act prohibiting the carrying of Weapons, concealed or other-wise, § 3: That it shall be the duty of the sheriffs, their deputies, or constables, to arrest and take all persons who shall be found with deadly weapons of the class and description mentioned in the first section of this act, and present them to some justice of the peace, or other authority, to be examined; and it shall also be the duty of the judges of the district courts to cause, at the first term to be held in each county, the sheriffs and their deputies to take an oath that they will truly and faithfully comply with the provisions of this act, and that they will arrest at all times every person who shall violate any of the provisions of this act.
Keywords: BRANDISHING; DISCHARGE